Influence of CrossFit exercises on the power abilities of high school pupils - Anhelina Petrova; Tetiana Bala (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to determine the influence of CrossFit exercises on the power abilities of high school-age children. Materials and methods: theoretical analysis and generalization of scientific and methodological literature, pedagogical testing, pedagogical experiment, and methods of mathematical statistics. Such tests as the lifting of straight legs hanging (number of times); bending and extension of hands lying on the floor (number of times); triple jump on the right and left leg (m) were used to determine the level of the strength development of the 10th-11th-grade pupils. The studied results were compared to norms and evaluated with a certain number of points. Statistical analysis: the research materials were processed using the licensed program Excel. The study involved 113 schoolchildren in grades 10-11. Results: at the beginning of the school year, we conducted the stating experiment, according to the results of which it was established below the average level of development of power abilities in high school pupils. According to the results of the primary research, pupils were assigned to the main and control groups for further conducting the forming experiment. Pupils of control groups were engaged only in the generally accepted state program on physical education for the 10th-11th grades of general secondary education institutions, and the educational process on physical education of pupils of the main groups was supplemented by the variant module "CrossFit" developed by us. According to the results of researches obtained after the introduction of the experimental technique into the educational process for physical education, it was determined that in schoolchildren of the main groups, the level of development of power abilities increased from below average to above average. Changes weren't found on the score scale in the test control groups. In the age aspect, there is mainly an improvement in results with age, both in the main and control groups (p>0,05). In the gender aspect, it was revealed, mainly, the reliable primacy of the data of boys over the indicators of girls (p< 0,05-0,001). Conclusions: significant positive changes were revealed in the indicators of the level of the strength development of the 10th-11th-grade pupils of the main groups, after using the experimental technique proposed by us in the educational process on physical education.